Shariah Governance and the Utilisation of Non-Halal Funds: The Role of Supervisory Boards in Indonesian Islamic Microfinance - M Taufiq; Muhammad Arif Hudaya; Ridwan Safari; Harisma Annisa Al Islam (STAI Al-Mas'udiyah, 2025)
This study examines the role of the Shariah Supervisory Board (DPS) in overseeing the utilisation of non-income funds (TBDSP) at BPRS Syarikat Madani, Riau Islands, Indonesia. Using a qualitative juridical-empirical method, it integrates normative analysis of DSN-MUI fatwas and statutory provisions with empirical insights from interviews with bank managers and DPS members. The findings reveal that TBDSP funds, mainly derived from late payment penalties, are classified as benevolent deposits and allocated for social purposes such as disaster relief, scholarships, Islamic education support, and Qardh al-Hasan loans, consistent with DSN-MUI Fatwa No. 123/2018 and the Board of Directors’ Decree No. 034/SK-DIR/X/2023. The DPS authorises major disbursements, ensures compliance with Shariah regulations, and monitors reporting to the Financial Services Authority. However, its supervisory role remains largely procedural, with limited evaluation of the social impact of fund utilisation. The study highlights the need to strengthen DPS capacity through standardised Shariah audit mechanisms and digital transparency tools to align practice with maqashid al-shariah. Theoretically, it extends Shari’ate Enterprise Theory by emphasising the integration of impact evaluation into Shariah governance and positioning DPS as both a compliance guardian and a driver of institutional legitimacy in Islamic microfinance.